A study on factors influencing job satisfaction among employees of Pharmaniaga Group, Bukit Raja / Nurul Asyikeen Harith - Harith, Nurul Asyikeen (2010)
In present age of modern technology and growing transformation in organizational culture, job satisfaction has emerged to be very significant component of management strategies. Success of effective human resources strategies greatly rely upon how well employees are being treated in that organization. In short, job satisfaction is a pleasure that an employee draw from his job. The past researcher shows that there are many factors that influence employee’s job satisfaction. Present research study revealed that there are five factors that could be the tools to retain employees which are pay, promotion, supervision, colleagues and the work itself. This study has been conducted within Pharmaniaga Group Bukit Raja and it involved 50 respondents in different departments. Results of the present study showed that the most influential factors that affects employee’s job satisfaction is the relationship with colleagues. It also shows that colleagues have a positive relationship with employee’s job satisfaction in Pharmaniaga Group, Bukit Raja. Recommendations for future research are also been discussed.